Rancang Bangun Turbin Model Gorlov Sebagai Pembangkit Listrik Tenaga Pikohidro (PLTPH) Memanfaatkan Energi Arus Aliran Sungai - Wildan Nur Rohman; George Endri Kusuma; Tri Andi Setiawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Electrical energy is an important source of energy for the community. In producing the majority of electricity still using coal burning which has a negative impact on breathing, the solution to the problem of pollution is to use renewable energy. PLTPH is one of the sources of electrical energy. The potential of PLTMH in Central Java is 75,926 kW. The construction of a hydroelectric power plant is expensive, overseas manufacturing a turbine costs about 99 million rupiah. In this study using the Ulrich method, where this method compares 3 design concepts with four chosen criteria, namely the fabrication process, portability, dimensions, and costs. Making this design using autodesk fusion software, the fabrication cost of this tool is Rp 4,740,700.00 with details of the cost of raw materials of Rp. Rp. 3,748,700.00, direct labor costs of Rp. 625,000.00, Overhead costs of367,000.00. Performance tests carried out in rivers that have a water velocity of 0.8 m / s and a river width of 4 meters, obtained the results of a turbine rotation without a load of 300 rpm measured using a tachometer.